Electronic Games to Reduce Child Pain Levels With Injection of Circumcision Anesthesia - Tunggul Sri Agus Setyaningsih; Hesti Wahyuni (Universitas Muhammadiyah Semarang, 2020)
Circumcision is an action done by removing the skin that covers the tip of the penis. The pain will be felt during the child is injected circumcision anesthesia. This can make the child uncooperative, making it difficult for the procedure to be performed. Electronic games are one of the non-pharmacological management to reduce pain in children. The purpose of this study was to identify the effect of the use of electronic games on the level of pain in children undergoing circumcision anesthetic injection. This research uses quantitative method, quasi-experimental research with one group pretest-posttest design. The technique used is an accidental sampling. The study was conducted on 17 children who performed circumcision anesthesia injections in Klinik Kencana Medika Rancaekek Bandung. Pain response is measured using the Faces Pain Rating Scale. These results indicate that there are significant differences with p-value <0.001 and alpha significance value £ 0.05. Based on the results of the study showed the use of electronic games affects the level of pain in children who performed injection circumcision anesthesia. Electronic games can reduce the level of pain in children who undergo injection of circumcision anesthesia. It is hoped that the use of electronic games can be done on factors that affect the level of pain.